Multi-criteria analysis of porous asphalt mixtures with aramid fiber under adverse conditions - Delafuente Navarro, Christopher; Lastra González, Pedro; Slebi Acevedo, Carlos José; Indacoechea Vega, Irune; Castro Fresno , Daniel (My University, 2024)
This study the functional performance of super porous asphalt mixtures with two types of aramid fibers against adverse events during their service life. This research was organized in 4 phases: first, particle loss after extreme weather conditions was evaluated. Second, the permeability and clogging resistance was assessed. Third, its resistance to fuel spillage was studied. Fourth, a multi-criteria analysis was performed to determine the best performing mixture considering all the studied variables. Regarding the results, mixture with aramid and polyolefin was the best performing blend according to the multi-criteria analysis. The fiber content allowed for acceptable performance in terms of particle loss despite having a higher void content than the reference mixtures. In addition, a higher permeability and clogging resistance was found, so the use of such fibers did not negatively affect the internal structure of the mixture. Finally, it had a higher resistance to fuel spillage due to the use of polymer-modified bitumen.

Este estudio el desempeño funcional de mezclas asfálticas superporosas con dos tipos de fibras de aramida frente a eventos adversos durante su vida útil. Esta investigación se organizó en 4 fases: primero, se evaluó la pérdida de partículas después de condiciones climáticas extremas. Segundo, se evaluó la permeabilidad y la resistencia a la obstrucción. Tercero, se estudió su resistencia al derrame de combustible. Cuarto, se realizó un análisis multicriterio para determinar la mezcla de mejor desempeño considerando todas las variables estudiadas. Con respecto a los resultados, la mezcla con aramida y poliolefina fue la mezcla de mejor desempeño según el análisis multicriterio. El contenido de fibra permitió un desempeño aceptable en términos de pérdida de partículas a pesar de tener un mayor contenido de vacíos que las mezclas de referencia. Además, se encontró una mayor permeabilidad y resistencia a la obstrucción, por lo que el uso de dichas fibras no afectó negativamente la estructura interna de la mezcla. Finalmente, tuvo una mayor resistencia al derrame de combustible debido al uso de betún modificado con polímeros.
Digital
Keywords: Asfalto; Asphalt; Hormigón asfáltico; Asphalt concrete; Porosidad; Porosity; High porous asphalt; Fibers; Polymer modified binder; Multi-criteria analysis